Evaluation of Chitosan; a Thermosensitive Hydrogel Drug Delivery Agent for Loading Dexamethosone - Hasnain Muhammad Buksh, Hussain Ahmad Khaqan, Muhammad Yar Usman Imtiaz, Atteq-ur-Rehman (Pakistan Journal of Ophthalmology, 2019)
Correspondence to: Hussain Ahmad Khaqan Lahore General Hospital, IRCBM (Interdisciplinary Research Centre and Biomedical Materials) COMSATS Institute of Information Technology, Lahore, Pakistan Email: drkhaqan@hotmail.com Purpose: To evaluate the characteristics of thermosensitive hydrogel (Chitosan) drug delivery agent loaded with dexamethasone/chitosan which can be used in the treatment of macular edema and non infectious uveitis applied in sub tenon space. Study Design: Quasi experimental study. Place and Duration of Study: Lahore General hospital, IRCBM COMSATS Institute of Information Technology, Lahore, Pakistan from July 2017 to July 2018. Material and Methods: Acetic acid (0.5 M, 2.5 ml) and Chitosan (0.2g) were dissolved and stirred for 1 hour and 30 minutes at room temperature. Powdered dexamethasone (3.5 mg) was added and stirred for further 30 min at room temperature. This solution was placed at 4°C for 30 min to cool it down. After this, NaHCO3 solution (0.48 M, 2 ml) was added drop wise. Once required pH was achieved, solution was placed inside oven at 37°C. Formation of gel started after 3-5 minutes and it took 2 hours for complete conversion of liquid into hydrogel. Results: The gelling time of the synthesized gel was 2 hours and was tested by test tube invert method. To prove the non-irritancy of thermosensitive hydrogel, Hens Egg Test on Chorioallantoic membrane assay (HET-CAM) was performed. Results showed that synthesized hydrogel was non-irritant. Outcomes